The Diversity of Rot Fungi from Cocoa Plantation and Its Ability to Grow on Carbon Source Media - Iradhatullah Rahim; Suherman Suherman; Andi Nasaruddin (Universitas Muhammadiyah Yogyakarta, 2019)
Rot fungi are microorganisms that can degrade biomass, especially biomass containing carbon. This fungus can decompose wood components (lignocelluloses) into simpler compounds. This research aimed to determine the diversity of rot fungi that have fruit body and grow in cocoa plantation as well as to observe their morphology and ability to grow on carbon source media. Fruiting body was taken from decayed cocoa stems from the farmers’ cocoa plantation in Bila Village, Pitu Riase, Sidrap Regency, South Sulawesi. The fruiting body then was sterilized and grown on the PDA medium.. The isolates then were morphologically characterized and grown on a solid Czapek dox medium containing carbon source of lignin, chitin, cellulose, and pectin. The rot fungi from Basidiomycota found were Mycena spp, Lycoperdon spp, Auricularia spp, Schizophyllum spp, Coprinus spp, Tremella spp, Crepidopus spp, Trametes spp, and Pleurotus spp. The different growth abilities were characterized by the large diameter of the colony formed. The highest colony diameter of Lycoperdon spp was on cellulose media, while that of Tremella spp was on the three other media. The results show that the rot fungi from cocoa plant have a large potential to be used as biodecomposer.